2020
DOI: 10.1007/s00300-020-02700-8
|View full text |Cite
|
Sign up to set email alerts
|

Autumn to spring microbial community in the northern Baltic Sea: temporal variability in bacterial, viral and nanoflagellate abundance during the cold-water season

Abstract: Marine microbial communities undergo drastic changes during the seasonal cycle in high latitude seas. Despite the dominance of microbial biomass in the oceans, comprehensive studies on the seasonal changes of microbial plankton during the complete winter period are lacking. To study the seasonal variation in abundance of the microbial community, water samples were collected weekly in the Northern Baltic Sea from October to May. During ice cover from mid-January to April, samples from the sea ice and the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…This suggests that sialic acid metabolism might instead be linked to nutrient utilization. Phytoplankton and fungi tend to be prevalent in the Baltic Sea during summer times when the temperature is above 10°C (Kaikkonen et al, 2020). These eukaryotes have peripheral sialic acid that could act as a stimulus for sialic acid metabolising bacteria to exploit this resource.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that sialic acid metabolism might instead be linked to nutrient utilization. Phytoplankton and fungi tend to be prevalent in the Baltic Sea during summer times when the temperature is above 10°C (Kaikkonen et al, 2020). These eukaryotes have peripheral sialic acid that could act as a stimulus for sialic acid metabolising bacteria to exploit this resource.…”
Section: Discussionmentioning
confidence: 99%
“…To separate this drift from trends induced by environmental or biotic processes in the time series [ 36 ], asymmetric eigenvector maps (AEMs) and local contributions to beta diversity (LCBD) were generated, following Appendix S2 of Legendre and Gauthier [ 48 ]. Values of sea-ice and water temperature, salinity, nutrients, algal biomass and chlorophyll a were taken from Enberg et al [ 36 ] and values of bacterial abundance and productivity from Kaikkonen et al [ 49 ]. Irradiance and air temperature were retrieved from the Photovoltaic Geographical Information System ( https://ec.europa.eu/jrc/en/pvgis ) 21 September 2020, and a weekly average (7-day period prior to the sampling time) of the daily irradiance and air temperature was calculated for each sampling time.…”
Section: Methodsmentioning
confidence: 99%
“…Heterotrophic protists and viruses are deemed as the most significant factors causing bacterioplankton losses in the ocean (Giorgio et al, 1996; Suttle, 2007) through size‐selective grazing and host‐specific lysis activities, respectively, regulating the flow of energy and organic matter through the planktonic food web (Liu et al, 2015). Attempts have been made to determine the impact of top‐down control on prokaryotic communities in both marine and fresh water ecosystems [e.g., the coastal Mediterranean Thau lagoon in Bouvy et al, 2011; or groups of temperate lakes in France (Ram et al, 2014)], suggesting that the relative impact of heterotrophic nanoflagellates (HNFs) and viruses on bacterioplankton communities can vary in different environments, often resulting in spatial (e.g., Kopylov et al, 2021) and temporal (e.g., Kaikkonen et al, 2020) variability. Tsai et al (2013) suggested that grazing by HNF was the main source of bacterioplankton mortality during summertime, while viral lysis was responsible for most bacterial losses during the colder months in the subtropical W Pacific Ocean.…”
Section: Introductionmentioning
confidence: 99%